Proceedings of the 4th International Congress on Sport Sciences Research and Technology Support 2016
DOI: 10.5220/0006085400890095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pedobarographic Profile in Young Males with Left and Right Scoliotic Posture

Abstract: Background: Scoliosis alters both posture and gait. Pedobarography is a biomechanical method for assessing gait that has been rarely used in scoliosis-specific gait research. Objective: To determine differences between left and right scoliotic posture in plantar pressure and force gait profile among young males. Methods: Twenty-one young, trained males assigned to one of two groups: left scoliotic posture (LSP; N=12) and right scoliotic posture (RSP; N=9) group. Subjects were assigned to a group based on forwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Contrary to findings of Aydina et al, 2015, i.e. there is no clinically significant correlation between clinical scores and static pedobarographic measurements, and of Gruić, et al 2016., i.e. plantar pressure and force gait parameters seem to have no diagnostic value in determining scoliosis-specific gait, initial findings in this research, within forward stepwise regression analysis, found clear statistical multiple correlation between clinical scores and dynamic pedobarographic measurements.…”
Section: Discussionmentioning
confidence: 56%
“…Contrary to findings of Aydina et al, 2015, i.e. there is no clinically significant correlation between clinical scores and static pedobarographic measurements, and of Gruić, et al 2016., i.e. plantar pressure and force gait parameters seem to have no diagnostic value in determining scoliosis-specific gait, initial findings in this research, within forward stepwise regression analysis, found clear statistical multiple correlation between clinical scores and dynamic pedobarographic measurements.…”
Section: Discussionmentioning
confidence: 56%